Novel polymorphisms in CYP4A22 associated with susceptibility to coronary heart disease - Kang Huang; Tianyi Ma; Qiang Li; Zanrui Zhong; Yilei Zhou; Wei Zhang; Ting Qin; Shilin Tang; Jianghua Zhong; Shijuan Lu (BMC, 2024)
Abstract Background Coronary heart disease (CHD) has become a worldwide public health problem. Genetic factors are considered important risk factors for CHD. The aim of this study was to explore the correlation between CYP4A22 gene polymorphism and CHD susceptibility in the Chinese Han population. Methods We used SNPStats online software to complete the association analysis among 962 volunteers. False-positive report probability analysis was used to confirm whether a positive result is noteworthy. Haploview software and SNPStats were used for haplotype analysis and linkage disequilibrium. Multi-factor dimensionality reduction was applied to evaluate the interaction between candidate SNPs. Results In overall and some stratified analyses (male, age ≤ 60 years or CHD patients complicated with hypertension), CYP4A22-rs12564525 (overall, OR = 0.83, p-value is 0.042) and CYP4A22-rs2056900 (overall, OR = 1.22, p-value is 0.032) were associated with the risk of CHD. CYP4A22-4926581 was associated with increased CHD risk only in some stratified analyses. FPRP indicated that all positive results in our study are noteworthy findings. In addition, MDR showed that the single-locus model composed of rs2056900 is the best model for predicting susceptibility to CHD. Conclusion There are significant associations between susceptibility to CHD and CYP4A22 rs12564525, and rs2056900.